Spatiotemporal interactions of a novel mesocarnivore community in an urban environment before and during SARS‐CoV‐2 lockdown. Issue 2 (23rd November 2021) - Louvrier, Julie L. P.; Planillo, Aimara; Stillfried, Milena; Hagen, Robert; Börner, Konstantin; Kimmig, Sophia; Ortmann, Sylvia; Schumann, Anke; Brandt, Miriam; Kramer‐Schadt, Stephanie
Abstract: Studying species interactions and niche segregation under human pressure provides important insights into species adaptation, community functioning and ecosystem stability. Due to their high plasticity in behaviour and diet, urban mesocarnivores are ideal species for studying community assembly in novel communities. We analysed the spatial and temporal species interactions of an urban mesocarnivore community composed of the red fox Vulpes vulpes and the marten Martes sp. as native species, the raccoon Procyon lotor as invasive species, and the cat Felis catus as a domestic species in combination with human disturbance modulated by the SARS‐CoV‐2 lockdown effect that happened while the study was conducted. We analysed camera trap data and applied a joint species distribution model to understand not only the environmental variables influencing the detection of mesocarnivores and their use intensity of environmental features but also the species' co‐occurrences while accounting for environmental variables. We then assessed whether they displayed temporal niche partitioning based on activity analyses, and finally analysed at a smaller temporal scale the time of delay after the detection of another focal species. We found that species were more often detected and displayed a higher use intensity in gardens during the SARS‐CoV‐2 lockdown period, while showing a shorter temporal delay during the same period, meaning a high human‐induced spatiotemporal overlap. All three wild species spatially co‐occurred within the urban area, with a positive response of raccoons to cats in detection and use intensity, whereas foxes showed a negative trend towards cats. When assessing the temporal partitioning, we found that all wild species showed overlapping nocturnal activities. All species displayed temporal segregation based on temporal delay. According to the temporal delay analyses, cats were the species avoided the most by all wild species. To conclude, we found that although the wild species were positively associated in space, the avoidance occurred at a smaller temporal scale, and human pressure in addition led to high spatiotemporal overlap. Our study sheds light to the complex patterns underlying the interactions in a mesocarnivore community both spatially and temporally, and the exacerbated effect of human pressure on community dynamics. Abstract : This study contains many dimensions of ecological dynamics: human–wildlife interactions and human activities effects, ecological niche theory, species interactions and community assembly. In an urban environment, mesocarnivores displayed similar spatial requirements, their activities were concentrated during the night and the partitioning appears at a smaller temporal scale.